The interdependence between regulatory functions and health attitudes in preschool children, characterized by varying degrees of involvement in organized motor activity - Dobrina E.V.; Gerasimova E.N. (Theory and Practice of Physical Culture, 2025)
Objective of the study aims to establish a correlation between the development of executive functions and the perception of health by children aged 5-6 years engaged in organized and unorganized motor activity. Methods and structure of the study. In the course of the work, 100 children aged 5 to 6 years were examined. Of these, 45 attended kindergarten and various sports clubs, forming a group with organized physical activity. The remaining 55 children did not attend kindergarten or sports clubs, representing a group with disorganized motor activity. To assess the attitude to health, an adapted questionnaire was used by R.A. Berezovskaya Street, where certain formulations were adjusted to take into account age, for example, "Happy family life" was transformed into "Good relations with parents", and "Interesting work, career" – into "Successful studies at school". The study of executive functions included an assessment of sensorimotor integration using the ReBOS technique, which makes it possible to evaluate the characteristics of simple and complex sensorimotor reactions. Results and conclusions. The analysis of the results revealed a five-factor structure. The first factor, which explains 29.8% of the variance of the trait, is most closely related to the parameters of motor activity, attitude to health and executive functions. Regression analysis demonstrated the relationship between executive functions, in particular, the parameters of simple and complex sensorimotor reactions, and various aspects of the attitude to health in older preschool children. Thus, regular motor activity is associated with the peculiarities of health perception and physiological manifestations of selective behavior in older preschoolers.